THE NATURE OF EXISTENCE, AS CONCEPTUALIZED IN PHILOSOPHY AND NATURAL SCIENCES, ENCOMPASSES VARIOUS CONCEPTIONS - Mustafayev Jafar Shomirzayevich; Mamatqobilov Shahriyor Shodmon o`g`li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This scientific article explores the concepts related to the nature of probability in philosophy and the natural sciences. Through scientific research and theoretical analysis, the article investigates the nature of probability and its significant role in philosophy and the natural sciences. Key topics include the epistemological, ontological, and methodological foundations of probability, as well as its importance in the natural world and theoretical considerations thereof. The article discusses the uniqueness of probability and its impact on philosophy and the natural sciences, along with the methods used to study probability. As a result, the article presents further insights, challenges, and scientific approaches to deepen understanding of the nature of probability and its specificity in philosophy and the natural sciences.